PENGARUH GAYA KEPEMIMPINAN DAN PENGAMBILAN KEPUTUSAN TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI SELATAN - Halim, Ardiansyah; Akob, Reski Arianty; ., Gunawan; ., Susianah; ., Mursidah (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2022)
This study aims to determine the effect of leadership style on employee performance, and the influence of decision making on employee performance. Data collection used primary data obtained from employees at the Maritime Affairs and Fisheries Service of South Sulawesi Province which were then used as respondents using the slovin formula after carrying out calculations so that the researchers adjusted as many as 66 respondents. The results of the data collected through the distribution of the questionnaire have been tested with classic assumption tests in the form of normality assumptions, multicollinearity assumptions, linearity assumptions and heteroscedasticity assumptions. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis using the SPSS Version 23 application. The results showed that leadership style has a positive and significant effect on employee performance at the Maritime Affairs and Fisheries Service of South Sulawesi Province. In addition, this study also shows that decision making has a positive and significant effect on employee performance at the Maritime Affairs and Fisheries Service of South Sulawesi Province so that all hypotheses proposed are accepted.